Kesesuaian Lahan Padang Rumput Imperata untuk Penggembalaan Di Provinsi Maluku Utara - Dahlia Aprilia Soraya; Ramli Hadun; Amiruddin Teapon; Abdurrahman Hoda (Jurnal Pertanian Khairun, 2022)
Imperata land usually left abandoned. Destruction of forest and abandonend land impacted to the expansion of the imperata lands. Imperata lands also trigger a fire. Therefore, this research pushed utilization of imperata lands for grazing.This research to study data of land sustainability and recommendation for development of grazing. Methodology used are purposive random sampling technic of land survey by spatial mapping and followed by physical and chemical test of soils.Â The suitable land for beef cattle herding system 2.114,8 ha, 1.822,9 ha for cowshed system, 1.822,7 ha for the development of animals forage, 1.557,0 ha for dry food producing plants, and 1.298,0 ha for peanut plants.Keywords: Land suitability, imperata, grazing.